Influence of Crown and Abutment Material on the Color of All-ceramic Screw-retained Implant Fixed Prosthesis. - Chiang, Jackie. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Posthodontics.; Advisor: Kiho Kang.; Committee: Yong Jeong Kim, Khaled El Rafie, Gabriela Lagreca, Yukio Kudara, and Sarah Pagni.; Keyword: Dentistry.